Early Modern French Autobiography - Virastau, Nicolae Alexandru, author.
1 online resource.
Keywords: "This book offers a survey of the constitution of the French memoir tradition, and explores in detail the works of four representative authors: Philippe de Commynes, Louise de Savoie, Philippe de Cheverny, and François de Bassompierre. Works of self-writing were usually printed under the title of "memoirs" and have been often considered a uniform genre. These early forms of self-writing were in fact highly heterogenous works at the crossroads of multiple genres, from the account book to the astrological diary. Their writing, printing, and circulation challenge modern notions of autobiographical genres: their authorship is often questionable and collective, and they tended to be compiled in large collections for political ends, without regard to the authors' intention"--